New Insights into Foodborne Bacteria–Host Interactions: Evolving Research and Discoveries - Anja Klančnik; Maja Abram (Microorganisms, 2023)
Given the growing concern about foodborne diseases, intensive research and the development of new approaches are crucial [...]